East Meets West? Board Characteristics in an Emerging Market: Evidence from Turkish Banks - Kaymak, Turhan; Bektas, Eralp (Wiley, 2008)
Manuscript Type: Empirical Research Question/Issue: The aim of this study is to uncover whether prescribed western style governance practices surface in the characteristics of board of directors in Turkish banks, and to see if these characteristics influence firm performance. Turkey is an emerging market drawing large amounts of foreign investment but board composition issues have rarely been analyzed. Research Findings/Results: This study investigates the association of board independence, CEO duality, board size, and board tenure with bank performance in Turkey. These relationships are examined for all 27 Turkish banks operating in the market between the years 2001-2004. Our findings suggest that the presence of insiders has a positive impact on return on assets, while duality and board tenure are negatively associated with performance. Theoretical Implications: Our study shows that Turkish banks are following a number of recommended governance practices, but the prevalence of some arrangements may exacerbate principal-principal conflict. Whether this holds in other more closed sectors of the economy is an area worthy of further investigation. Practical Implications: The presence of duality in the form of duly empowered members/executive directors is very problematic, leading to potential principal-principal conflict. Strategic investors and portfolio managers should challenge this arrangement before making sizable outlays in the Turkish financial sector.
Keywords: Corporate Governance; Board of Directors; Corporate Performance; Banking; Central and Eastern Europe